Student Engagement Among Undergraduate Students in Southeast Asia: Systematic Literature Review - Brigitta Dyah Utami Immanuella; Farida Kurniawati; Tjut Rifameutia (Yayasan Keluarga Guru Mandiri, 2023)
Southeast Asia has up to 7,000 higher education institutions with various qualities. The inequality may affect the learning process, such as student engagement. Student engagement is a multidimensional construct that is often positively related to academic achievement. This systematic review aims to get an overview and factors that influence undergraduate students' engagement in Southeast Asian countries. The article search method was carried out through five online databases; ERIC, ProQuest, Scopus, SpringerLink, and Taylor Francis Online, and obtained 11 articles. The articles were extracted using PRISMA flow. As a result, student engagement in Southeast Asia can be described through several dimensions, namely cognitive, emotional, behavioral, and agentic. The theory most widely used is Self-Determination and Social Cognitive Theory. Besides, there are also Broaden-and-Build Theory, Conservation of Resources, and Tinto Integration Model used as the theoretical framework in some studies. For the predictors, undergraduate student engagement in Southeast Asia is more influenced by external factors that will lead to the appearance of internal predictors. Furthermore, these results also show that several demographic factors can be influential, such as age and generation group, university type, and cultural factors. The implication of this study is to consider generational and cultural characteristics to gain a deeper analysis of student engagement. The researchers also provide recommendations for further research, especially for increasing external influence to gain student engagement towards undergraduates.